Kitesurfing and snowkiting injuries in Norway: a retrospective study - Venke Torland; Øyvind Thomassen; Øyvind Østerås (BMC, 2024)
Abstract Background Kiteboarding (kitesurfing on water and snowkiting) is a fairly new sport and is defined as a high-risk sport. The injury rate has been reported to be between 6 and 9 per 1000 h. The aim of the study was to identify and describe kiteboarding-related injuries in Norway over a five-year period. Methods We used "snowball sampling" to identify kiteboarding accidents in a retrospective study. In addition, we conducted structural searches in the National Air Ambulance Service and Search and Rescue Helicopter patient record databases. All included informants were interviewed. Descriptive methods were used to characterise the sample. Results Twenty-nine kiteboarders were included, with a total of 33 injuries. One half of the injuries to head, face and neck were cerebral concussions (n = 12). The most common type of injury was bone fractures (n = 28), followed by soft tissue injuries (n = 24). Most injuries were of moderate severity (51%) and falling from less than 5 m was the most common mechanism of injury. Operator error and lack of experience were the most frequently reported causes of accidents (82%). Conclusions Serious injuries occured during kiteboarding. The majority of kiteboarders reported operator error or lack of experience as the cause of their accident. Prior to kiteboarding, a course highlighting the importance in using helmet for snowkiting and both helmet and life vest in kitesurfing, should be mandatory.